Trypanosoma cruzi: establishment of permeable cells for RNA processing analysis with drugs - Ambrósio, DL [UNESP]; Barbosa, CF [UNESP]; Vianna, VF [UNESP]; Cicarelli, RMB [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2004)
Pre-mRNA maturation in trypanosomatids occurs through a process called trans-splicing which involves excision of introns and union of exons in two independent transcripts. For the first time, we present the standardization of Trypanosoma cruzi permeable cells (Y strain) as a model for trans-splicing study of mRNAs in trypanosomes, following by RNase protection reaction, which localizes the SL exon and intron. This trans-splicing reaction in vitro was also used to analyze the influence of NFOH-121, a nitrofurazone-derivative, on this mechanism. The results suggested that the prodrug affects the RNA processing in these parasites, but the trans-splicing reaction still occurred.
Keywords: trans-splicing; Trypanosoma cruzi; NFOH-121 (hydroxymethylnitrofurazone)